2003
DOI: 10.2355/isijinternational.43.915
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electromagnetic Brake and Meniscus Electromagnetic Stirrer on Transient Molten Steel Flow at Meniscus in a Continuous Casting Mold

Abstract: On the molten steel flow in the mold of the slab-type continuous caster, the analysis by the unsteady and three-dimensional mathematical model is carried out from the viewpoint of the meniscus behavior. As flow control methods at meniscus in the mold, electromagnetic brake and meniscus electromagnetic stirrer are chosen, and those flow control characteristics are investigated and results are as follows.1) The electromagnetic brake makes the molten steel flow two-dimensional, and the turbulence of fluid flow is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 15 publications
(19 reference statements)
4
19
0
Order By: Relevance
“…(2), various turbulent models, such as Prandtl mixing-length-type model, 2) one-equation model, 1) low-Reynolds [7][8][9][10]14) and high-Reynolds [3][4][5]11,13) number two-equation k-e models, and large eddy simulation model 15) have been proposed in the modeling of the continuous casting solidification process. Although some investigation suggested that the numerical treatments of turbulent models and its suppression approach affected the mushy zone, 14,27,28) a realizable k-e turbulent model equations, 12,29) which possibly better describes the mold flow with higher turbulent Reynolds number and predicts the spreading rate of SEN impinging jets in a thin slab casting at higher casting speed, is used in this study.…”
Section: Numerical Analysis Methods 31 Mathematical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2), various turbulent models, such as Prandtl mixing-length-type model, 2) one-equation model, 1) low-Reynolds [7][8][9][10]14) and high-Reynolds [3][4][5]11,13) number two-equation k-e models, and large eddy simulation model 15) have been proposed in the modeling of the continuous casting solidification process. Although some investigation suggested that the numerical treatments of turbulent models and its suppression approach affected the mushy zone, 14,27,28) a realizable k-e turbulent model equations, 12,29) which possibly better describes the mold flow with higher turbulent Reynolds number and predicts the spreading rate of SEN impinging jets in a thin slab casting at higher casting speed, is used in this study.…”
Section: Numerical Analysis Methods 31 Mathematical Modelsmentioning
confidence: 99%
“…However, most of mathematical models were focused on the analysis of fluid flow, heat transfer and solidification in the conventional slab/billet mold without EMBR [1][2][3][4][5][6][7][8][9][10][11][12] or with EMBR. [13][14][15] In terms of numerical analysis of thin-slab casting process, [16][17][18][19][20][21][22][23] O'Connor et al 16) analyzed thermo-mechanical state in the funnel-type mold of CSP thin-slab caster. Camporredondo et al 17) performed an extensive experimental and modeling study to elucidate the thermal evolution of thin slabs during their passage through the mold and secondary cooling system of a CSP caster by a 2D curvilinear coordinate unsteady-state heatconduction model.…”
mentioning
confidence: 99%
“…The model has been validated by water model and by the low melting point alloy experiments. K. Takatani 43) has further developed his model and shown the effect of port angle, argon flow, electromagnetic brake and electromagnetic stirrer on the meniscus behavior. In the spray cooling zone, variables are nozzle type, water pressure, nozzle to nozzle distance, nozzle to strand surface length and strand surface area cooled by water spray.…”
Section: )mentioning
confidence: 99%
“…4) As a good example, I would like to draw attention to complex CFD predictions being carried out by Dr. Kouji Takatani and fellow researchers in his research laboratory at SMI, using some 240 computers, all working on parts of the numerical solutions, in parallel with one another, allowing for extremely fine grids. 5) Even under these best of circumstances, there will still remain many instances of uncertainty in predicting just what happens in complex two phase flow problems such as slag droplet entrainment into liquid steels, or three phase flows such as bottom bubbling, foaming, iron droplet-laden, slags in BOF's. CFD predictions of such phenomena are likely to be wrong, in the absence of supporting experimental data and observations.…”
Section: The Theory Of Fluid Flowsmentioning
confidence: 99%